Effect of Camellia sinensis plant on decreasing the level of halitosis: A systematic review - Bahareh Tahani; Roya Sabzian (Wolters Kluwer Medknow Publications, 2018)
Tea is the second most consumed beverage. Polyphenolic catechins of green tea have a number of beneficial effects in oral cavity. This study aims to evaluate the clinical effects of green tea on halitosis through a systematic review of available literature. All available randomized, clinical trials - with a relevant subject that met the inclusion criteria - were included by searching PubMed, Cochrane, ProQuest, and Google Scholar, and Scopus databases. To score the selected articles, 27 items of CONSORT 2010 checklist were considered. Each article was reviewed by all the authors. Searching the PubMed database yielded 42 articles, 2 of which met the inclusion criteria. None of the 12 articles were obtained through Cochrane library, and 85 articles retrieved from ProQuest database met the inclusion criteria. Three hundred and five articles were obtained from Google Scholar, three of which fulfilled the inclusion criteria. Two articles were omitted because they were duplicated, and the rest were excluded. Searching the Scopus database yielded 270 articles, 2 of which met the inclusion criteria, but they were also duplicated. Finally, two studies were selected according to the inclusion criteria of the study. In both of the included articles, the early effect of green tea use was statistically significant in comparison with baseline. One of the studies showed the long-term effect of green tea mouthwash. Green tea can reduce halitosis through rinsing and antimicrobial effect.